1995
DOI: 10.1074/jbc.270.38.22522
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Human Type II Receptor for Bone Morphogenetic Protein-4 That Forms Differential Heteromeric Complexes with Bone Morphogenetic Protein Type I Receptors

Abstract: Bone morphogenetic proteins (BMPs) comprise the largest subfamily of TGF-␤-related ligands and are known to bind to type I and type II receptor serine/ threonine kinases. Although several mammalian BMP type I receptors have been identified, the mammalian BMP type II receptors have remained elusive. We have isolated a cDNA encoding a novel transmembrane serine/threonine kinase from human skin fibroblasts which we demonstrate here to be a type II receptor that binds BMP-4. This receptor (BRK-3) is distantly rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
136
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 224 publications
(138 citation statements)
references
References 38 publications
2
136
0
Order By: Relevance
“…These results indicate that the truncated BMPR-IB does not bind BMP-2 with a high affinity in C2C12 cells. Interestingly, Nohno et al (27) reported that a truncated BMPR-II (BRK-3) did not efficiently cross-link to 125 I-BMP-4 when expressed alone in COS cells. However, coexpression of the truncated BMPR-II with the type I receptor enhanced the binding to 125 I-BMP-4.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These results indicate that the truncated BMPR-IB does not bind BMP-2 with a high affinity in C2C12 cells. Interestingly, Nohno et al (27) reported that a truncated BMPR-II (BRK-3) did not efficiently cross-link to 125 I-BMP-4 when expressed alone in COS cells. However, coexpression of the truncated BMPR-II with the type I receptor enhanced the binding to 125 I-BMP-4.…”
Section: Discussionmentioning
confidence: 99%
“…2 This suggests that the BMP-2 signals are transduced by the complex of BMPR-IA and BMPR-II in these cells. It was reported that both BMPR-IA and BMPR-IB formed complexes with BMPR-II or DAF-4, a type II receptor for a homologue of BMP-2/BMP-4 in C. elegans, in a ligand-dependent manner when overexpressed together on the surface of COS cells (21,22,(25)(26)(27). In contrast to the truncated BMPR-IA, the kinase domain-truncated BMPR-IB did not inhibit the BMP-2 signaling in C2C12 cells even if its mRNA was abundantly expressed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three type I receptors have been shown to bind BMP ligands, type IA and IB BMP receptors (BMPR-IA or ALK-3 and BMPR-IB or ALK-6) and type IA activin receptor (ActR-IA or ALK-2) (Koenig et al, 1994;ten Dijke et al, 1994;Macias-Silva et al, 1998). Three type II receptors for BMPs have also been identified and they are type II BMP receptor (BMPR-II) and type II and IIB activin receptors (ActR-II and ActR-IIB) (Yamashita et al, 1995;Nohno et al, 1995;Rosenzweig et al, 1995;Kawabata et al, 1995). Whereas BMPR-IA, IB, and II are specific to BMPs, ActR-IA, II, and IIB are also signaling receptors for activins.…”
Section: Introductionmentioning
confidence: 99%
“…Three type II receptors, BMPR2 and the activin type II receptors ActRIIa and ActRIIb (12)(13)(14)(15)(16)(17), can pair with three different type I receptors, ActRIa/ALK2, BMPRIa/ALK3, and BMPRIb/ALK6 (13, 18 -23), to transduce BMP signals. These various BMP receptors have distinct temporal and spatial expression in tissues and have varying affinities for each of more than 15 known BMP molecules (1,24).…”
Section: Bone Morphogenetic Protein (Bmp)mentioning
confidence: 99%